2023
DOI: 10.1021/acs.jpcc.3c05407
|View full text |Cite
|
Sign up to set email alerts
|

Double Alkyl Side Chains Functionalized Polyimide as Gate Dielectrics for Application in Organic Transistors

Jiawei Zou,
Baotieliang Wang,
Bo Yu
et al.

Abstract: Compared with inorganic dielectrics, polymer-based gate dielectrics have received growing attention due to their flexibility, structural adjustability, and low cost in organic thin-film transistors (OTFTs) devices. Aromatic polyimides (APIs) stand out because of their outstanding thermal stability, structural diversity, mechanical flexibility, and large-area processability. In this work, we designed and prepared three API gate dielectrics by the low-temperature chemical imidization method. These API materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Organic thin-film transistors (OTFTs) are one of the most promising devices in organic electronics due to their flexibility, solution processability, lightweight, and low fabrication cost, which makes them have wide application potential in wearable and stretchable devices, radio frequency identification, nonvolatile memory, various sensors, etc. 1–5 Organic semiconductors 6,7 and polymer gate dielectrics, 8,9 as core components of the OTFT, have become the key to optimizing device performance in the last two decades. In particular, for regular bottom-gate top-contact OTFT devices, it is of great importance to develop gate dielectric materials that are compatible with organic semiconductors, as carrier transport occurs at the dielectric layer and semiconductor interface, which are directly related to the mobility and operation voltage of OTFTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic thin-film transistors (OTFTs) are one of the most promising devices in organic electronics due to their flexibility, solution processability, lightweight, and low fabrication cost, which makes them have wide application potential in wearable and stretchable devices, radio frequency identification, nonvolatile memory, various sensors, etc. 1–5 Organic semiconductors 6,7 and polymer gate dielectrics, 8,9 as core components of the OTFT, have become the key to optimizing device performance in the last two decades. In particular, for regular bottom-gate top-contact OTFT devices, it is of great importance to develop gate dielectric materials that are compatible with organic semiconductors, as carrier transport occurs at the dielectric layer and semiconductor interface, which are directly related to the mobility and operation voltage of OTFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the introduction of fluorine-containing structures into the PI chains, the addition of bulky side units to the polymer skeleton is also an important approach to effectively improve the performance of OTFTs. Zou and co-workers 4,24 synthesized a series of modified aromatic diamine monomers containing single or double different lengths of alkyl side chains and the corresponding functionalized PI-derived dielectric materials. They found that the appropriate length of the alkyl side chain helped to improve the compatibility between the PI and the organic semiconductor, leading to better interfacial properties and overall device performance.…”
Section: Introductionmentioning
confidence: 99%